Obseg pleistocenske poledenitve na Lovčenu v Črni gori - Stepišnik, Uroš (Geografski vestnik, 2010)
The massif of Lovčen is a most southern part of the mountain range Zunanji Dinaridi. In the Pleistocene, its surface was highly reformed by glacial processes. Based on the detailed morphographic mapping of glacial features, the extent of glaciation was determined as being far larger than described in previous references. The inner part of the Lovčen was covered with an ice field from where tongues of ice were flowing out. Moraine and fluvioglacial material filled the karstic basins of the Njeguši Polje and Cetinje Polje. The lowest moraines of outlet glaciers were found on the western side of Bay of Kotor at sea level, which until now, was the lowest known moraine material of the last glacial maximum within the Mediterranean.
Keywords: geomorfologija; geomorphology; relief; topography; krasoslovje; pleistocen; Črna gora; Lovčen